Photoinduced Dearomative Multiple Functionalization of Quinolines to Construct Highly Substituted 3D Frameworks - Shimose, Asuha; Nagashima, Yuki (Synlett, 2025)
Dearomative functionalization of quinolines expands the chemical diversity of highly functionalized 3D frameworks, such as 1,2,3,4- and 5,6,7,8-tetrahydroquinoline derivatives, which are important pharmacophores, with minimal synthetic costs. In this short review, we cover recent reports on the visible-light-induced dearomative functionalization of quinolines with an emphasis on reaction design/strategies and mechanistic studies and provide a theoretical basis for developing further dearomative syntheses in the future.1 Introduction2 Dearomative Functionalizations through the Formation of Photoexcited Quinolines3 Dearomative Functionalizations through the Formation of Photoexcited Reagents/Intermediates4 Conclusion
Keywords: dearomative functionalization; photoinduced reactions; quinoline; tetrahydroquinoline; 3D frameworks; mechanistic studies; DFT calculations